Effects of injectable progestogen contraception versus the copper intrauterine device on HIV acquisition: sub-study of a pragmatic randomised controlled trial. Issue 3 (5th April 2017) - Hofmeyr, G Justus; Singata-Madliki, Mandisa; Lawrie, Theresa A; Bergel, Eduardo; Temmerman, Marleen
Abstract : Background: Evidence from observational studies suggests an increased risk of HIV acquisition among women using depot medroxyprogesterone acetate (DMPA) contraception. Methods: Within the context of a South African programme to increase women's access to the intrauterine contraceptive device (IUD), we conducted a pragmatic, open-label, parallel-arm, randomised controlled trial (RCT) of the IUD versus injectable progestogen contraception (IPC) at two South African hospitals. The primary outcome was pregnancy; secondary outcomes included HIV acquisition. Consenting women attending termination of pregnancy services were randomised after pregnancy termination between July 2009 and November 2012. Condoms were promoted for the prevention of sexually transmitted infections. Voluntary HIV testing was offered at baseline and at 12 or more months later. Findings on HIV acquisition are reported in this article. Results: HIV acquisition data were available for 1290 initially HIV-negative women who underwent a final study interview at a median of 20 months after randomisation to IPC or an IUD. Baseline group characteristics were comparable. In the IPC group, 545/656 (83%) of participants received DMPA, 96 (15%) received injectable norethisterone enanthate, 14 (2%) received the IUD and one received oral contraception. In the IUD group 609 (96%) received the IUD, 20 (3%) received IPC and 5 (1%) had missing data. According to intention-to-treat analysis, HIV acquisition occurred in 20/656 (3.0%) women in the IPC arm and 22/634 (3.5%) women in the IUD arm (IPC vs IUD, risk ratio 0.88; 95% confidence interval 0.48–1.59; p =0.7). Conclusions: This sub-study was underpowered to rule out moderate differences in HIV risk, but confirms the feasibility of randomised trial methodology to address this question. Larger RCTs are needed to determine the relative risks of various contraceptive methods on HIV acquisition with greater precision. Trial registration number: Pan African Clinical Trials Registry number PACTR201409000880157 (04-09-2014).